2009
DOI: 10.1021/cb900099e
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Malonyl CoA-ACP Transacylase Binding of Streptomyces coelicolor Fatty Acid Synthase Acyl Carrier Protein

Abstract: Malonylation of an acyl carrier protein (ACP) by malonyl Coenzyme A-ACP transacylase (MCAT) is fundamental to bacterial fatty acid biosynthesis. Here, we report the structure of the Steptomyces coelicolor (Sc) fatty acid synthase (FAS) ACP and studies of its binding to MCAT. The carrier protein adopts an alpha-helical bundle structure common to other known carrier proteins. The Sc FAS ACP shows close structural homology with other fatty acid ACPs and less similarity with Sc actinorhodin (act) polyketide syntha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
47
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 36 publications
(79 reference statements)
6
47
1
Order By: Relevance
“…The VinK wild type was shown to bind VinL with a K a value of 8.2 ± 0.8 × 10 4 M −1 (Table 1 and Fig. S4A), which is similar to the affinities of other MCATs for ACPs (19,20). The R153A, M206A, and R299A mutants showed significantly reduced affinity for VinL (Fig.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…The VinK wild type was shown to bind VinL with a K a value of 8.2 ± 0.8 × 10 4 M −1 (Table 1 and Fig. S4A), which is similar to the affinities of other MCATs for ACPs (19,20). The R153A, M206A, and R299A mutants showed significantly reduced affinity for VinL (Fig.…”
Section: Resultssupporting
confidence: 57%
“…In terms of the interaction of AT with ACP, Streptomyces coelicolor MCAT was suggested to recognize the helix II of FAS ACP, based on the previous docking and mutational studies (19). However, the details of the binding and binding interface remain elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the Glu and Asp residues in helix II of Ec-ACP are important to recognize FabA, FabB, FabD, FabG, MCAT, AcpS, and FabH (61,(65)(66)(67)(68) Fig. 4A.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of streptomycete fatty acid synthesis (FAS)-which is closely linked to polyketide synthesis (PKS)-were conducted with S. coelicolor or S. glaucescens (16)(17)(18)(19)(20)(21)(22)(23)(24)(25). These bacteria utilize the dissociated FAS II system and have a highly conserved fab gene cluster consisting of fabD, fabH, acpP, and fabF.…”
mentioning
confidence: 99%